MODEL PERTANIAN URBAN BERBASIS DAUR ULANG: PELATIHAN BUDIDAYA SAWI DENGAN PIPA DAN BOTOL BEKAS DI KELURAHAN PEGUYANGAN: OPTIMIZATION OF PIPE, SOIL, AND RECYCLED BOTTLES INTEGRATION FOR URBAN MUSTARD GREEN CULTIVATION THROUGH TRAINING - Ghalda Syadza Rafa Nafisah; Putu Putri Prawitasari (LPPM Universitas Abdurrab, 2025)
Urban farming serves as an innovative solution to overcome the limitations of agricultural land in urban areas. This study aims to optimize the integration of pipes, soil, and used drinking bottles as an efficient method for cultivating mustard greens in Peguyangan Subdistrict through implementation at Uma Palak Lestari. This system is designed to enhance the efficiency of land, water, and plastic waste use to create a sustainable farming method applicable in urban environments with limited land availability. By using 50 recycled plastic bottles and 6 horizontal PVC pipes, the system was able to produce approximately 5.8 kilograms of mustard greens in a single planting cycle. Success was measured based on the yield, the plant growth rate (with 86% of planting holes successfully producing crops), and the active participation of 14 community members. The results show that the combination of pipes as a horizontal planting medium, soil as the primary nutrient source, and used drinking bottles as planting containers effectively supports mustard green growth. Furthermore, this method contributes to reducing plastic waste and improving urban food security. By utilizing recycled materials and a simple system, this approach has the potential to be replicated in various urban areas to support sustainable agriculture. Therefore, this innovation can serve as an eco-friendly, space-efficient, and sustainable plant cultivation model that contributes to urban ecosystem sustainability.